School Principal Leadership Management In Increasing Teacher Quality Through Classroom Action Research: An Islamic Education Perspective - H.Soro, Suharyanto; Komara, Endang; Wardoyo, Susilo; Dahlan, Elon (Eduprof : Islamic Education Journal, 2025)
Leadership management in educational units plays a crucial role in enhancing educational quality, particularly within Islamic education contexts where leaders must integrate spiritual values with professional development. School principals are required to motivate and guide educators to maximize their potential by actualizing the teaching-learning process through Islamic principles of amanah (trustworthiness), tawhid (unity), and qiwamah (stewardship). One effective approach educators can utilize to enhance learning quality is conducting classroom action research (CAR). However, the implementation of leadership in Islamic educational settings requires a contextually-sensitive approach that aligns with both Islamic values and modern pedagogical principles. School principals face difficulties maximizing educators' professional abilities if the management approach implemented does not align with the school environment and Islamic educational philosophy. This research aims to discover the leadership management approaches of school principals in increasing teacher quality through classroom action research within an Islamic education framework. Researchers employed a qualitative research paradigm with a case study approach. Data collection methods included observation, interviews, and documentation. The sample consisted of 10 Islamic teachers selected through purposive sampling, including the school principal, supervisors, and Islamic teachers. Data analysis utilized three steps: data reduction, data display, and conclusion drawing. The research findings indicated: (1) The school principal's leadership management is applied proportionally through an Islamic values-based collaborative model that integrates spiritual leadership with pedagogical supervision; (2) The school principal believes that classroom action research serves as a transformative approach aligned with Islamic principles of continuous improvement (istiqamah) and knowledge pursuit (thalab al-'ilm); (3) The TAGI (Take and Give) model, rooted in Islamic reciprocity principles, is applied to realize and maximize educator professionalism, thereby enabling the achievement of learning objectives and superior accreditation for the educational unit.